PEREMPUAN MINANGKABAU DALAM PANGGUNG POLITIK - Lindayanti Lindayanti (Universitas Negeri Yogyakarta, 2019)
Women in the Minangkabau indigenous community structure have a unique role. In the Minangkabau matrilineal custom system, women are placed ina central position. Minangkabau women have been portrayed as having played arole in the political arena in Minangkabau for a long time. This can be seen fromclassic Minangkabau stories such as kaba, tambo or myth. Many stories ofwomen's heroism are found. What is the relationship between the ideal level andreality in the politics of Minangkabau women? For example,